Micro-drops and digital microfluidics - Berthier, Jean (William Andrew, 2013)
Explores the fundamentals and applications of digital microfluidics, enabling engineers and scientists to design this important enabling technology into devices and harness the considerable potential of digital microfluidics in testing and data collection.